The Zebrafish Antiapoptotic Protein BIRC2 Promotes Edwardsiella piscicida Infection by Inhibiting Caspases and Accumulating p53 in a p53 Transcription-Dependent and -Independent Manner - Cao, Lu; Yan, Dong; Xiao, Jun; Feng, Hao; Chang, Ming Xian (Frontiers in Immunology, 2021)
IAPs (inhibitors of apoptosis) are endogenous caspase inhibitors with multiple biological activities. Our recent study has revealed antibacterial property of the pro-apoptotic protein BID. In the present study, we show functional characteristics of antiapoptotic protein BIRC2 (cIAP1) in response to Edwardsiella piscicida infection. Overexpression of BIRC2 in zebrafish larvae promoted the proliferation of E. piscicida, leading to a decreased larvae survival. The expression levels of caspases including casp3, casp8 and casp9 were significantly inhibited by BIRC2 overexpression in the case of E. piscicida infection. Treatment of zebrafish larvae microinjected with BIRC2 with the caspase activator PAC-1 completely blocked the negative regulation of BIRC2 on the E. piscicida infection, with the reduced inhibition on the casp3 and without inhibition on casp8 and casp9. In contrast to the regulation of BIRC2 on the caspases, BIRC2 overexpression significantly induced the expression of p53, especially at 24 hpi. In addition to the cytoplasmic p53 expression, BIRC2 overexpression also induced the expression of the nuclear p53 protein. Further analysis demonstrated that BIRC2 could interact and colocalize with p53 in the cytoplasm. The numbers of E. piscicida in larvae overexpressed with BIRC2 and treated with pifithrin-μ (an inhibitor of mitochondrial p53) or pifithrin-α (an inhibitor of p53 transactivation) were lower than those of larvae without pifithrin-μ or pifithrin-α treatment. Critically, the p53 inactivators pifithrin-μ and pifithrin-α had no significant effect on larval survival, but completely rescued larval survival for zebrafish microinjected with BIRC2 in the case of E. piscicida infection. Collectively, the present study suggest that piscine BIRC2 is a negative regulator for antibacterial immune response in response to the E. piscicida infection via inhibiting caspases, and accumulating p53 in a p53 transcription-dependent and -independent manner.